1997
DOI: 10.1063/1.473589
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of abrupt shape transition in ferrogels induced by nonuniform magnetic field

Abstract: Unidirectional elongation of magnetic field sensitive polymer gels, called ferrogels, have been studied. In ferrogels, finely distributed colloidal particles having superparamagnetic behavior are incorporated into a swollen network. These particles couple the shape of the gel to the nonuniform magnetic field. Shape distortion occurs instantaneously and disappears when the external field is removed. A discontinuous elongation and contraction in response to infinite-small change in the external magnetic field ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 7 publications
(6 reference statements)
5
97
0
2
Order By: Relevance
“…Anisotropic, field-induced structure in a colloidal suspension can be locked in to place using chemical gelation, yielding an anisotropic magnetic gel or "ferrogel". [5][6][7] The properties of ferrogels can also be inferred from knowledge of the field-dependent PDF; in earlier work, this has been achieved by computer simulations, 8,9 but already a more general theory of ferrogel a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic, field-induced structure in a colloidal suspension can be locked in to place using chemical gelation, yielding an anisotropic magnetic gel or "ferrogel". [5][6][7] The properties of ferrogels can also be inferred from knowledge of the field-dependent PDF; in earlier work, this has been achieved by computer simulations, 8,9 but already a more general theory of ferrogel a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%
“…The coupling between the soft elastic medium and the magnetic NPs allows the manipulation of the volume and shape of the ferrogels through the application of external magnetic fields. The effects of the magnetic fields on strain (Faidley et al 2010), shape (Raikher and Stolbov 2005;Zrínyi et al 1997), water retention François et al 2007), stiffness (Mitsumata et al 1999), and the effect of the polymeric matrix on the structural and magnetic properties (Longo et al 2012) have been reported. Because of these properties, ferrogels have many potential applications in the fields of pharmaceutics and medicine as biomembranes, biosensors, artificial muscles, and matrices for drug delivery, among others (Furukawa et al 2003;Gonzalez et al 2012;Liu et al 2006;Mao et al 2005;Miyata et al 2002;Pich et al 2004;Qiu and Park 2001;Sivudu and Rhee 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on a hydrogel's structure and chemical composition, its dimensions can change in response to alterations in environmental temperature, [11][12][13] pH, [14][15][16][17][18][19] ionic strength, 20 21 electric field, 22 23 magnetic field, 24 light, 25 26 or concentration of specific analytes. [27][28][29][30] When mechanically constrained, responsive hydrogels exert swelling forces on the constraining structures.…”
Section: Introductionmentioning
confidence: 99%